PENETRATING ABDOMINAL MISSILE INJURIES ANALYTIC STUDY IN RAMADI TEACHING HOSPITAL - Salam Adil Salih; Nabil Isam Naiem; Mohammed Abdullah Mohammed; Firas Kamel Al-Azawii (Scholar Express Journals, 2022)
The aim of this study to the penetrating missile injuries to the abdomen was to analyze the organs affected by these injuries and to evaluate the efficacy and necessity of the current treatment modalities. This prospective clinical trial conducted in Ramadi Teaching Hospital, Accident and Emergency (A and E) Department and the surgical unit. Starting from the 1st of October 2017 to 30th of September 2019. for 174 patients admitted to the (A and E) department with abdominal missile injury, we categorized those with associated injuries to other anatomical body areas, lines of treatments, those underwent laparotomies and statistically analyzing intra-abdominal organs injuries. The results revealed that: The most vulnerable age group involved between 21-30 years comprised 54.02% of total. Male to female ratio = 6.90:1. It was observed that majority of the injuries were high velocity missile (HVM). and shrapnel (44.25%), while low velocity missile (LVM) as pistol (17.81%). It was seen that 84.84% of patients had positive findings during laparotomies. Small intestine was involved in majority of the patients (42.85%), followed by large intestine in 35.71%, then Liver in 19.04%. Majority of the patients had involvement of three organs (34.53%), followed by involvement of two organs (32.14%). Plain (alone) abdominal missile injuries were found in 56.89% of total patients. Associated injuries of two or more than two body regions/areas were found in minority of patients (7.47%). P. Value was 0.003. And the mortality was 1.14% also it was found that 65 (32%) of the patient with missile abdominal injuries were treated conservatively and 15 (8.6%) had negative laparotomies .so we concluded that about 40% of the patient with missile abdominal injury had no significant intra-abdominal injury which could be managed non-operatively ; Since unnecessary laparotomy is associated with morbidity and prolongation of hospital stay duration
Keywords: Abdominal missile trauma; high velocity missile; low velocity missile